Unprecedented insights into extents of biological responses to physical forcing in an Arctic sub-mesoscale filament by combining high-resolution measurement approaches - Weiß, Josefine Friederike; von Appen, Wilken-Jon; Niehoff, Barbara; Hildebrand, Nicole; Graeve, Martin; Neuhaus, Stefan; Bracher, Astrid; Nöthig, Eva-Maria; Metfies, Katja (Scientific reports, 2024)
In Fram Strait, we combined underway-sampling using the remote-controlled Automated Filtration System for Marine Microbes (AUTOFIM) with CTD-sampling for eDNA analyses, and with high-resolution optical measurements in an unprecedented approach to determine variability in plankton composition in response to physical forcing in a sub-mesoscale filament. We determined plankton composition and biomass near the surface with a horizontal resolution of ~ 2 km, and addressed vertical variability at five selected sites. Inside and near the filament, plankton composition was tightly linked to the hydrological dynamics related to the presence of sea ice. The comprehensive data set indicates that sea-ice melt related stratification near the surface inside the sub-mesoscale filament resulted in increased sequence abundances of sea ice-associated diatoms and zooplankton near the surface. In analogy to the physical data set, the underway eDNA data, complemented with highly sampled phytoplankton pigment data suggest a corridor of 7 km along the filament with enhanced photosynthetic biomass and sequence abundances of sea-ice associated plankton. Thus, based on our data we extrapolated an area of 350 km 2 in Fram Strait with enhanced plankton abundances, possibly leading to enhanced POC export in an area that is around a magnitude larger than the visible streak of sea-ice.